2022
DOI: 10.3389/feart.2022.808503
|View full text |Cite
|
Sign up to set email alerts
|

Large-to Local-Scale Control of Pre-Existing Structures on Continental Rifting: Examples From the Main Ethiopian Rift, East Africa

Abstract: In the Main Ethiopian Rift (East Africa) a complex tectonic history preceded Tertiary rifting creating pre-existing discontinuities that influenced extension-related deformation. Therefore, this area offers the opportunity to analyze the control exerted by pre-existing structures on continental rifting at different scales. In this paper we present an overview of such an influence. We show that at a large scale (up to ∼800–1,000 km) rift localization has been controlled by a lithospheric-scale inherited heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 136 publications
(182 reference statements)
1
15
0
Order By: Relevance
“…(2020) suggested that triple junction dynamics in the Afar region likely did not cause the formation of the MER, this latter being related to a later and independent rifting event. This sequence is broadly supported by the majority of geological studies which suggest initiation of the Red Sea‐ Gulf of Aden rifting since 34 Ma, and the MER initiating at 10–20 Ma (e.g., Corti et al., 2022; Girdler, 1984; Watchorn et al., 1998; Wolfenden et al., 2004; Pik et al., 2013, and reference therein). Therefore, both our analog and numerical models, in agreement with other Authors (e.g., Almalki & Betts, 2021; Khalil et al., 2020, 2021), indicate that a simple single‐stage, symmetric dynamic does not explain the structural pattern nowadays observed at the Afar triple junction, and its migration through time.…”
Section: Discussionmentioning
confidence: 58%
“…(2020) suggested that triple junction dynamics in the Afar region likely did not cause the formation of the MER, this latter being related to a later and independent rifting event. This sequence is broadly supported by the majority of geological studies which suggest initiation of the Red Sea‐ Gulf of Aden rifting since 34 Ma, and the MER initiating at 10–20 Ma (e.g., Corti et al., 2022; Girdler, 1984; Watchorn et al., 1998; Wolfenden et al., 2004; Pik et al., 2013, and reference therein). Therefore, both our analog and numerical models, in agreement with other Authors (e.g., Almalki & Betts, 2021; Khalil et al., 2020, 2021), indicate that a simple single‐stage, symmetric dynamic does not explain the structural pattern nowadays observed at the Afar triple junction, and its migration through time.…”
Section: Discussionmentioning
confidence: 58%
“…imparted by Proterozoic orogenic events in East Africa, as observed, for example, in the Malawi (Ring, 1994;Laó-Dávila et al, 2015;Dawson et al, 2018;Hodge et al, 2018;Kolawole et al, 2018;Williams et al, 2019;Scholz et al, 2020;Shillington et al, 2020;Wedmore et al, 2020b), Albertine (Katumwehe et al, 2015), Kivu (Smets et al, 2016), Kenya (Smith and Mosley, 1993;Robertson et al, 2016;Muirhead and Kattenhorn, 2018), the Main Ethiopian (Corti et al, 2022),…”
Section: Applying the Structural Inheritance Framework To The East Af...mentioning
confidence: 99%
“…The East African Rift System (EARS) is the pre-eminent example of an active continental rift, exhibiting all stages of continental rift evolution from nascent seafloor spreading in Afar to incipient faulting in the Okavango Rift of Botswana (Figure 10a;McConnell, 1972;Chorowicz, 2005;Ebinger, 2005;Macgregor, 2015;Daly et al, 2020). Hard-and soft-linked structural inheritance has influenced the evolution of the EARS at many spatial scales (and also magma emplacement mechanisms and volcanic activity; see Corti et al, 2022 for examples from the Main Ethiopian Rift). A famous example of plate-scale inheritance is present south of the Main Ethiopian Rift, where the Eastern and Western Branches of the EARS wrap around the relatively rigid Archean Tanzanian craton and spatially co-locate with orogenic belts that formed during the progressive Proterozoic amalgamation of the African Continent (Figure 10a; Daly et al, 1989;Versfelt and Rosendahl, 1989;Nyblade and Brazier, 2002;Corti et al, 2007).…”
Section: Applying the Structural Inheritance Framework To The East Af...mentioning
confidence: 99%
See 2 more Smart Citations